Addition reaction curable organopolysiloxane composition and method for producing same
By using the organopolysiloxane composition at a specific ratio and a small amount of platinum group metal-based catalyst, the problems of high platinum catalyst amount and insufficient curing in the prior art are solved, and efficient and low-cost peelable coating formation is achieved.
Patent Information
- Application Number
- CN202380067770.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, in order to form a peelable coating, a higher amount of platinum group metal-based catalyst is required, resulting in high cost and the presence of catalyst toxins affecting the curing reaction.
The addition reaction curing was performed by using two organopolysiloxanes (A-1) and (A-2) at a specific ratio, which had polyalkenyl and a small amount of acryloyl group characteristics, respectively. The addition reaction was carried out to cure with (B) organohydrogen polysiloxane and (C) a small amount of platinum group metal-based catalyst to form a coating with good peeling force.
The addition reaction curing is achieved with a small amount of platinum group metal catalyst, forming a coating with a peeling force comparable to that of the traditional method, and at the same time, the formation of cyclic low-molecular silicones is inhibited, and the appearance of whitening and separation and settlement are avoided.
Smart Images

Figure BDA0005321998650000251 
Figure BDA0005321998650000261 
Figure BDA0005321998650000271
Abstract
Description
Technical Field
[0001] The present invention relates to an addition reaction curable organopolysiloxane composition capable of undergoing addition reaction even with a low amount of platinum, and a method for producing the same. Background Art
[0002] Conventionally, in order to prevent adhesion and fixation between sheet substrates such as paper and plastic and adhesive materials, a cured film of an organopolysiloxane composition is formed on the substrate surface to impart release properties. The following methods are known as methods for forming a cured organopolysiloxane film on the substrate surface. (1) A method of forming a releasable coating film by addition reaction of an alkenyl group-containing organopolysiloxane with an organohydrogenpolysiloxane using a platinum group metal compound as a catalyst. (2) A method of forming a releasable coating by causing an organopolysiloxane having a functional group such as a hydroxyl group or an alkoxy group to undergo a condensation reaction using an organic metal salt as a catalyst. (3) A method of forming a releasable coating by radically polymerizing an acryl group-containing organopolysiloxane and a photoreaction initiator using ultraviolet rays or electron beams.
[0003] Among the above (1), (2), and (3), the method for forming a peelable coating by an addition reaction using a platinum catalyst is widely used, which has excellent curability and can meet various peeling property requirements from low-speed peeling to high-speed peeling.
[0004] In the past, the amount of platinum group metal catalyst contained in the organopolysiloxane composition for release paper or release film was mostly 60 to 400 mass ppm in terms of platinum group metal concentration. If the platinum concentration is less than the above lower limit, the curing reaction does not proceed sufficiently, and the strength of the cured film is insufficient. In addition, the amount of residual Si-H groups increases, and the peeling force increases. Furthermore, the unreacted raw material organopolysiloxane exists, which becomes a migration component. The organopolysiloxane migrates to the pressure-sensitive adhesive surface attached to the release paper, which may cause a decrease in adhesion.
[0005] Furthermore, platinum group metals are rare and precious metals, so they are expensive. The proportion of platinum catalyst in the original price of release paper or release film manufacturing is large. Therefore, reducing the platinum group metal catalyst can reduce the price. In addition, the substrate contains components that become catalyst toxins of platinum group metal catalysts, such as nitrogen compounds, sulfur compounds, and phosphorus compounds. Sometimes, the catalyst toxin components are combined with platinum group metals, and curing by addition reaction no longer proceeds.
[0006] Therefore, a method for forming a peelable coating with a smaller amount of platinum is being sought. For example, Patent Document 1: Japanese Patent Gazette No. 4221300 describes a silicone composition comprising: a polyorganosiloxane having at least two alkenyl groups bonded to silicon atoms per molecule, a hydrogenated organosiloxane having SiH groups at the end and side chains, and an MDViQ resin and a hydrosilylation inhibitor as an adhesion regulating system. Patent Document 2: Japanese Patent Publication No. 2009-513740 describes a dissociation coating composition comprising an alkenyl functionalized polysiloxane, a hydrogenated silicon functionalized polysiloxane and a platinum group metal, wherein the alkenyl functionalized polysiloxane is prepared using a phosphazene base catalyst. However, the above composition is not sufficiently cured as described below.
[0007] For example, the composition described in Patent Document 1 is characterized in that a terminal SiH group with good reactivity and a film-forming MDViQ resin are used, and in an example, the composition is cured by heating it at 150°C for 1.8 seconds at a platinum concentration of 60 ppm. However, the extracted portion (the amount of unreacted siloxane) in the cured film cured at a platinum concentration of 60 ppm is as high as 5.8 to 6.5% by mass, and a large amount of uncured siloxane exists, and the curing is insufficient. In addition, there is no description of the peeling property in Patent Document 4.
[0008] The composition described in Patent Document 2 is characterized in that the alkenyl functionalized polysiloxane is a branched siloxane having MDQ units. It is described that the probability of producing a cross-linked coating is increased by using a branched chain having a terminal vinyl group. In the embodiment described in Patent Document 2, tetrakis(dimethylvinylsiloxy)silane is reacted with a phosphazene catalyst to synthesize a branched siloxane containing an alkenyl group, and then a silhydride functionalized polysiloxane and a platinum catalyst are mixed in an amount such that the platinum concentration becomes 40 ppm, and the composition is cured under the conditions of 100°C·15 seconds and 115°C·20 seconds. Patent Document 5 evaluates the cured state of the composition by extracting the cured product with methyl isobutyl ketone. The proportion of the extracted unreacted siloxane is as high as 6.4 to 25.2%, and the curing is insufficient. In addition, no other evaluations such as the peeling properties were performed.
[0009] In a fully cured coating, the amount of unreacted siloxane extracted is generally preferably 5% or less, and more preferably 3% or less. As described in the above-mentioned Patent Documents 4 and 5, if the amount of unreacted siloxane in the cured coating is more than 5%, the siloxane migrates to the surface of the paste, and the residual adhesion rate is greatly reduced. In addition, since a large amount of residual SiH groups remain, the peeling force is increased compared to the case of full curing. Therefore, an organopolysiloxane composition that can be cured with a small amount of platinum catalyst is sought.
[0010] Patent document 3: International Publication No. 2020 / 145151 found that when an organic polysiloxane compound having three or more (meth)acryloyl groups in one molecule and a weight-average molecular weight of 1000 or more is added to an addition reaction-type release paper silicone composition, an addition reaction can be carried out with a small amount of platinum group metal catalyst, and a cured film having the same release force as before can be formed.
[0011] The composition of Patent Document 3 is indeed excellent in curing properties even at low platinum levels of 15ppm and 20ppm, and there is little uncured silicone, but the compatibility of the organopolysiloxane containing an acryloyl group with other siloxanes (organopolysiloxane containing an alkenyl group and organohydrogenpolysiloxane) is poor, and although the composition is turbid when mixed, the organopolysiloxane containing an acryloyl group settles over time and settles and separates after standing for 10 to 60 minutes. If the lower layer is not well mixed, curing at a small amount of platinum group metal catalyst becomes insufficient.
[0012] It should be noted that the regulation of low molecular weight siloxanes has become stricter, and D4 and D6 have become monitored chemical substances in Japan. In addition, in Europe, D4, D5, and D6 are listed on the SVHC (Substances of Very High Concern) candidate list. From 2020, products containing 0.1% or more of low molecular weight siloxanes in products for personal care, cleaning, and detergents will be regulated, so it is required that the added amount of D4, D5, and D6 be less than 0.1% by mass, respectively. Prior art literature
[0013] Patent Literature Patent Document 1: Japanese Patent No. 4221300 Patent Document 2: Japanese Patent Application No. 2009-513740 Patent Document 3: International Publication No. 2020 / 145151 Summary of the invention Problems to be solved by the invention
[0014] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide an addition reaction-curable organopolysiloxane composition which can be cured by addition reaction with a small amount of platinum group metal catalyst, can form a cured film having a peeling force equivalent to that of the prior art, has a reduced amount of cyclic low molecular weight siloxanes such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane, and has a suppressed appearance of white turbidity and separation and sedimentation over time. Means of solving problems
[0015] The present inventors have conducted intensive research to achieve the above-mentioned object, and have found that, in an addition reaction curing type organopolysiloxane composition, by using a combination of (A-1) an organopolysiloxane having an average of 2 or more alkenyl groups bonded to silicon atoms per molecule and (A-2) an organopolysiloxane having an average of 0.1 or more and 20 or less (meth)acryloyl groups and an average of 0.1 or more alkenyl groups per molecule at a specific ratio, the addition reaction curing type organopolysiloxane composition can be cured by addition reaction with a small amount of platinum group metal catalyst, can form a cured film having the same peeling force as before, and can suppress the amount of cyclic low molecular weight siloxanes such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane. It was also found that by making the ratio specific, the compatibility of the above-mentioned components (A-1) and (A-2) is improved, and the turbidity of the appearance and the separation and sedimentation over time are suppressed, thereby completing the present invention.
[0016] Therefore, the present invention provides the following inventions. 1. An addition reaction curable organopolysiloxane composition comprising the following components (A), (B) and (C), (A)The following (A-1) and (A-2) (A-1) an organopolysiloxane having an average of 2 or more alkenyl groups bonded to a silicon atom in one molecule and having no (meth)acryloyl group: 50 to 99.9 parts by mass, (A-2) an organopolysiloxane having an average of 0.1 or more alkenyl groups and an average of 0.1 to 20 (meth)acryloyl groups in one molecule: 50 to 0.1 parts by mass, wherein the total of (A-1) and (A-2) is 100 parts by mass, (B) an organohydrogenpolysiloxane having an average of 2 or more hydrogen atoms bonded to silicon atoms (Si—H groups) in one molecule, (C) Platinum group metal catalyst: 1 to 200 ppm in terms of mass of platinum group metal relative to the total amount of the composition. 2. The addition reaction-curable organopolysiloxane composition according to 1, wherein the total content of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane is 1000 ppm (mass) or less of the component (A). 3. The addition reaction-curable organopolysiloxane composition according to 1 or 2, further comprising an addition reaction control agent as component (D). 4. The addition reaction-curable organopolysiloxane composition according to 3, wherein the component (D) comprises a mixture of an ethynyl group-containing compound having a hydroxyl group and a silane having an ethynyl group. 5. The addition reaction-curable organopolysiloxane composition according to any one of 1 to 4, which is used for release paper or release film. 6. A method for producing the addition reaction-curable organopolysiloxane composition according to 1 or 2, comprising the step of mixing (A-1), (A-2) and (B). 7. A method for producing the addition reaction-curable organopolysiloxane composition according to 3 or 4, comprising the step of preliminarily mixing and dispersing the component (D) in the components (A-1) and (A-2) or (B). 8. The production method according to 6 or 7, comprising a step of synthesizing component (A-1) using a base catalyst and a step of synthesizing component (A-2) using an acid catalyst. Effects of the Invention
[0017] Provided is an addition reaction curing type organopolysiloxane composition which can be cured by addition reaction with a relatively small amount of platinum group metal catalyst, can form a cured film having a peeling force equivalent to that of conventional films, can suppress the amount of cyclic low molecular weight siloxanes such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane, and can suppress white turbidity in appearance and separation and sedimentation over time. DETAILED DESCRIPTION
[0018] The present invention is described in detail below. [(A) ingredient] The component (A) of the present invention contains the following components (A-1) and (A-2). (A-1) an organopolysiloxane having an average of 2 or more alkenyl groups bonded to a silicon atom in one molecule and having no (meth)acryloyl group: 50 to 99.9 parts by mass, (A-2) Organopolysiloxane having an average of 0.1 or more alkenyl groups and an average of 0.1 to 20 (meth)acryloyl groups in one molecule: 50 to 0.1 parts by mass (the total of (A-1) and (A-2) is 100 parts by mass). (A-1) The organopolysiloxane having an average of 2 or more alkenyl groups bonded to a silicon atom in one molecule and having no (meth)acryloyl group may be used alone or in combination of two or more. Examples thereof include organopolysiloxanes having a structure represented by the following formula (1). M a M Vi b D c D Vi d T e T Vi f Q g (1) (Where, M is R3SiO 1 / 2 , M Vi For R2PSiO 1 / 2 , D is R2SiO 2 / 2 , D Vi RPSiO 2 / 2 , T is RSiO 3 / 2 , T Vi For PSiO 3 / 2 , Q is SiO 4 / 2 . R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and having no aliphatic unsaturated bond. h An alkenyl group represented by -CH=CH2 (h is an integer of 0 to 6). a, b, d, and f are each independently 0 or a positive number, b, d, and f are not 0 at the same time, a+b≥1, 2≤b+d+f≤500, c is a positive number between 10 and 2700, e is a positive number less than 0 or 200, and g is a positive number less than 0 or 100.)
[0019] In the above formula (1), R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and having no aliphatic unsaturated bond, preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms, and more preferably a monovalent hydrocarbon group having 1 to 8 carbon atoms. Specifically, the group includes: alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, and dodecyl; cycloalkyl groups such as cyclohexyl; aryl groups such as phenyl, naphthyl, and tolyl; aralkyl groups such as benzyl and phenethyl; and groups in which a part of the hydrogen atoms bonded to the carbon atoms of these groups are substituted with halogen atoms, epoxy groups, amino groups, polyether groups, cyano groups, hydroxyl groups, and the like. Among them, in order to reduce the curability and the peeling strength of the obtained cured product, it is preferred that 80 mol% or more of the total number of R is methyl.
[0020] P is -(CH2) h Alkenyl represented by -CH=CH2 (h is an integer of 0 to 6), and specifically includes vinyl, allyl, butenyl, propenyl, 5-hexenyl, octenyl, decenyl and the like, among which vinyl is preferred.
[0021] a, b, d, and f are each independently 0 or a positive number, b, d, and f are not 0 at the same time, a+b≥1, 2≤b+d+f≤500, c is a positive number of 10 to 2700, e is a positive number of 0 or less than 200, and g is a positive number of 0 or less than 100. a is preferably a positive number of 0 or less than 100, b is preferably a positive number of 0 or less than 100, d is preferably a positive number of 0 or less than 500, and f is preferably a positive number of 0 or less than 100. a+b≥1, preferably a+b≥2. 2≤b+d+f≤500, preferably 2≤b+d+f≤200. c is a positive number of 10 to 2700, preferably 30 to 2000, and more preferably 50 to 1500. When c is less than 10, the viscosity is too low, and the composition may flow down from the roller or scatter as droplets when the roller rotates, resulting in a significant reduction in the amount that can be applied to the substrate. e is a positive number of 0 or 200 or less, preferably a positive number of 0 or 20 or less, and more preferably a positive number of 0 or 10 or less. g is a positive number of 0 or 10 or less, and preferably a positive number of 0 or 5 or less.
[0022] Component (A-1) specifically includes: polysiloxanes containing alkenyl groups at both ends, polysiloxanes containing alkenyl groups at side chains, polysiloxanes containing alkenyl groups at one end and side chains, polysiloxanes containing alkenyl groups at both ends and side chains, and polysiloxanes containing branched alkenyl groups at terminal ends. Vi 2D c 、M2D c D Vi d 、M Vi 3D c T1, M Vi 4D c T2, M Vi 5D c T3, M Vi 2D c D Vi d 、M Vi 2D c Q1, M Vi 4D c Q1, M a D c D Vi d T Vi f (M, M Vi ,D,D Vi , T, T Vi , Q, a, c, d, f are the same as above. The same below. ) etc. As a more specific structural formula, there can be cited: M Vi 2D 155 、M Vi 2D 100 、M2D 97 DVi 3. M2D 62 D Vi 4. M2D 96 D Vi 4. M2D 95 D Vi 5. M Vi 3D 100 T1, M Vi 4D 100 T2, M Vi 2D 97 D Vi 1. M Vi 2D 95 D Vi 3. M3D 93 D Vi 3T Vi 1. M Vi 2D 2000 、M2D 1000 D Vi 20 wait.
[0023] The vinyl value of component (A-1) is preferably 0.001 to 0.7 mol / 100 g, more preferably 0.005 to 0.5 mol / 100 g, and even more preferably 0.01 to 0.1 mol / 100 g. If the vinyl value is less than 0.001 mol / 100 g, the number of reaction points is too small, and poor curing may occur. If the vinyl value exceeds 0.7 mol / 100 g, the crosslinking density is too high, and the low-speed peeling force may be increased.
[0024] The weight average molecular weight of (A-1) component is preferably 800 or more and 200,000 or less, more preferably 1000 or more and 150,000 or less, and further preferably 1500 or more and 100,000 or less. If the weight average molecular weight of (A-1) component is lower than 800, wettability is improved, and it is easy to expand, and it is possible that the coating amount on the substrate becomes insufficient. In addition, if it exceeds 200,000, it becomes difficult to wet and expand on the contrary, and it is possible that the coating amount on the substrate is unevenly distributed. It should be noted that in the present invention, the weight average molecular weight of (A-1) component is a measured value of the weight average molecular weight based on polystyrene conversion using gel permeation chromatography (GPC) analysis (solvent: toluene).
[0025] The kinematic viscosity of the component (A-1) at 25° C. measured with an Ostwald viscometer is preferably 7 mm 2 / s or more and 3 million mm 2 / s or less, more preferably 10 to 10000 mm 2 / s, more preferably 20 to 5000 mm 2 / s. When the kinematic viscosity is less than 7mm2 / s, the kinetic viscosity of the entire composition decreases, and the coating amount may become insufficient.
[0026] (A-2) An organopolysiloxane having an average of 0.1 or more alkenyl groups and an average of 0.1 to 20 (meth)acryloyl groups in one molecule can be used alone or in combination of two or more. It is noted that the alkenyl group is preferably bonded to a silicon atom, and preferably has 0.1 to 10 alkenyl groups in one molecule. The (meth)acryloyl group is preferably bonded to a silicon atom, and preferably has 0.1 to 15 alkenyl groups in one molecule. As component (A-2), for example, an organopolysiloxane having a structure represented by the following formula (2) can be mentioned. M α i M j D α k D L T α m T n Q q (2) (Where, M is R 3 SiO 1 / 2 , D is R 2 SiO 2 / 2 , T is RSiO 3 / 2 , Q is SiO 4 / 2 , M α AcR2SiO 1 / 2 :M Ac or R2PSiO 1 / 2 :M Vi , D α AcRSiO 2 / 2 :DM Ac or RPSiO 2 / 2 :D Vi , T α AcSiO 3 / 2 :T Ac or PSiO 3 / 2 :T Vi . R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and having no aliphatic unsaturated bond, and P is -(CH2) h -CH=CH2 (h is an integer from 0 to 6) represents an alkenyl group, Ac is CH2=CR 3 COOR 4 (R 3is a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, R 4 It is a divalent hydrocarbon group having 1 to 6 carbon atoms, may have a branched or cyclic structure, and may contain an epoxy group, an ester group, a urethane group, an ether group, an isocyanate group, or a hydroxyl group). i is a positive number of 0 to 4, j is 0 or a positive number of 0 to 7, and i+j is a number of 2 to 7. k is a positive number of 0.1 to 20, L is a positive number of 3 to 300, m and n are both 0 or a positive number of 0 to 10, and q is 0 or a positive number of 0 to 4. However, it is appropriately selected so that an average of 0.1 or more alkenyl groups and an average of 0.1 to 20 (meth)acryloyl groups are present in one molecule.)
[0027] i is a positive number of 0 to 4, j is 0 or a positive number of 0 to 7, and i+j is a number of 2 to 7. i is preferably 2 or 3, in which case j is preferably 0. k is a positive number of 0.1 to 20, preferably a positive number of 0.5 to 15, and more preferably a positive number of 1 to 12. When k is less than 0.1, if the amount of catalyst is reduced, the curing property may decrease. On the other hand, from the viewpoint of compatibility with (A-1), k is preferably 20 or less. L is a positive number of 3 to 300, preferably a positive number of 5 to 180, and more preferably a positive number of 10 to 160. m and n are both 0 or a positive number of 0 to 10, preferably 0 or a positive number of 0 to 6, and more preferably 0 or a positive number of 0 to 3. q is 0 or a positive number of 0 to 4. When q exceeds 4, the viscosity may increase excessively and the peeling force may increase.
[0028] Specific examples of the (A-2) organopolysiloxane compound include: Vi 2D5D Ac 3. M Vi 2D 20 D Ac 5. M Vi 2D 20 D Ac 5. M Vi 2D 30 D Ac 7. M Vi 2D 90 D Ac 1. M Vi 2D 90 D Ac 9. M Vi 2D Vi 1D 230 D Ac 7. M Vi 2D 25 D Ac 7. M Vi 2D 65 D Ac 15 、M Vi 2D265 D Ac 15 、M Vi 2D 61 D Ac 15 、M Vi 1M Ac 1D 10 D Ac 3. M Vi 2D 110 D Ac 7. M Vi 3D 20 D Ac 5T1, M Vi 2D 150 D Ac 10 、M Vi 3D 110 D Ac 6T1, M Vi 2D 170 D Ac 22 、M Vi 2D 170 D Ac 20 Q1, M AC 2D 20 D Vi 1. M2D Vi 1D 30 D Ac 1st, etc.
[0029] The vinyl value of the component (A-2) is preferably 0.001 to 0.3 mol / 100 g, more preferably 0.01 to 0.1 mol / 100 g.
[0030] The weight average molecular weight of the component (A-2) is preferably 3,000 or more and 100,000 or less, and more preferably 5,000 or more and 30,000 or less.
[0031] The kinematic viscosity of the component (A-2) at 25° C. measured by an Ostwald viscometer is preferably 10 to 10,000, more preferably 50 to 3000. If the kinematic viscosity is too low, the kinematic viscosity of the entire composition decreases, and the coating amount may become insufficient.
[0032] Even if the component (A-1) is concentrated under reduced pressure for a long time at high temperature, the structure is stable, so the amount of low molecular weight siloxanes can be reduced, and the total amount of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane (hereinafter sometimes recorded as D4, D5, D6) can be 1 to 150 ppm. In contrast, if the component (A-2) is concentrated under reduced pressure to a volatile component amount of less than 2% by mass, a large amount of microgels will be produced. The microgels will clog the pores of the filter paper, so filtering cannot be performed. At present, when the volatile component is controlled to be 3 to 5% by mass for production, the amount of D4, D5, and D6 detected by gas chromatography is 1000 to 30000 ppm in total. Therefore, the less the amount of the component (A-2), the more the amount of low molecular weight siloxanes can be reduced. The mixing ratio of (A-1) and (A-2) is 50 to 99.9 parts by mass of (A-1) and 50 to 0.1 parts by mass of (A-2) (wherein the total of (A-1) and (A-2) is 100 parts by mass). That is, (A-1): (A-2) = 50:50 to 99.9:0.1. A more preferred range is (A-1): (A-2) = 70:30 to 99.8:0.2, and a further preferred range is (A-1): (A-2) = 80:20 to 99.5:0.5.
[0033] The total content of cyclic siloxanes such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane in the component (A) is preferably 1000 ppm (mass) or less (0.1 mass % or less), and more preferably 800 ppm or less. The quantitative determination of the amount of cyclic low molecular weight siloxane is performed by gas chromatography, using a capillary column, a temperature rise condition of 50°C to 280°C, a carrier gas of helium, a detector of FID, and a sample injection volume of 2 μL. As long as the total content of the above cyclic siloxanes in the component (A) is within the above range, the total content of the above cyclic siloxanes in the silicone composition can be in the range of 0.1 to 850 ppm, which is very effective.
[0034] (A-1) and (A-2) are preferably mixed thoroughly. This is because, when there is a bias in the presence of components having an acryloyl group, sometimes the part where curing is performed and the part where curing is not performed appear to be coated. Therefore, the mixture of (A-1) and (A-2) is preferably stirred for more than 30 seconds. Furthermore, when mixing (A-1) and (A-2), the component (D) described later can be mixed and dispersed.
[0035] (A-1) and (A-2) can be obtained by mixing the raw materials of the siloxane units, polymerizing and equilibrating them using an acid or base catalyst. For example, component (A-1) is often prepared by using a base catalyst such as KOH to polymerize M2 and M Vi 2. D4, D5, D Vi4 and the like, and heated and equilibrated. It is preferably prepared by using a base catalyst for the synthesis of (A-1) and an acid catalyst for the synthesis of (A-2). When a platinum catalyst is added to the silicone used as a release paper to prepare a cured film, for example, if the base catalyst used as the synthesis catalyst of (A-1) remains, it becomes a catalyst poison for the platinum catalyst and may hinder the curing. Even if the base catalyst remains at the ppb level, it shows a curing inhibitory effect. Therefore, when an acid catalyst is used as the synthesis catalyst of (A-2), a trace amount of the remaining base catalyst becomes a salt, which inhibits the curing inhibitory effect. Examples of the base catalyst include: KOH, NaOH, potassium silicate, cesium hydroxide, potassium methoxide, potassium tert-butoxide, potassium trimethylsiliconate, tetramethylammonium hydride, tetrabutyl hydroxide Examples of the acid catalyst include sulfuric acid, hydrochloric acid, methanesulfonic acid, and trifluoromethanesulfonic acid.
[0036] [(B) ingredient] (B) component is an organohydrogenpolysiloxane having an average of more than 2 hydrogen atoms (Si-H groups) bonded to silicon atoms in one molecule, and one type can be used alone or two or more types can be used in appropriate combination. Preferably, there are 3 to 200 hydrogen atoms (Si-H groups) bonded to silicon atoms in one molecule, and more preferably 10 to 200. The Si-H group of the organohydrogenpolysiloxane is subjected to an addition reaction with the alkenyl group of the (A) component to form an organopolysiloxane crosslinked product. As for the Si-H group content, it is preferably 0.001 to 3.5 mol / 100 g, more preferably 0.01 to 2.5 mol / 100 g, and further preferably 0.02 to 2.0 mol / 100 g. If the Si-H group content is too little, the curing property and adhesion may deteriorate, and if it is too much, the peeling force may become heavier.
[0037] The organohydrogensiloxane as the component (B) preferably has a structure represented by the following formula (3). M r M H s D t D H u T v T H w Q x (3) (Where, M is R3SiO 1 / 2 , M H For R2HSiO 1 / 2 , D is R2SiO 2 / 2 , D H RHSiO2 / 2 , T is RSiO 3 / 2 , T H For HSiO 3 / 2 , Q is SiO 4 / 2 . Each R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and having no aliphatic unsaturated bond. r, s, t, and v are each independently 0 or a positive number, u is 0 or a positive number less than 200, w is 0 or a positive number less than 10, x is 0 or a positive number less than 10, s, u, and w are not 0 at the same time, and 2≤s+u+w≤200. )
[0038] In the above formula (3), R can be exemplified by the same groups as R in the above formula (1), and an alkyl group having 1 to 8 carbon atoms is preferred. In the formula (3), r, s, t, and v are each independently 0 or a positive number, r is preferably a positive number of 0 or 10 or less, s is preferably a positive number of 0 or 10 or less, t is preferably a positive number of 0 or 100 or less, and v is a positive number of 0 or 10 or less, and preferably a positive number of 0 or 5 or less. In addition, u is a positive number of 0 or 200 or less, and preferably 2 to 100, and more preferably 10 to 80. w is a positive number of 0 or 10 or less, and preferably a positive number of 0 or 5 or less. In addition, s, u, and w are not 0 at the same time, and s+u+w is a positive number of 2 to 100, and preferably a positive number of 10 to 80. x is a positive number of 0 or 10 or less, and preferably a positive number of 0 or 5 or less.
[0039] Specific examples of the organohydrogenpolysiloxane of the component (B) include polysiloxanes containing hydrosilyl groups at both ends, polysiloxanes containing hydrosilyl groups at side chains, polysiloxanes containing hydrosilyl groups at one end and in side chains, and polysiloxanes containing hydrosilyl groups at both ends and in side chains.
[0040] If expressed in structural formula, we can cite: M H 2D t 、M2D H u 、M2D t D H u 、M H 2D t D H u 、M H 3D t T1, M H 4D t T2、MiD t D H u T H w (M, MH ,D,D H , T, T H , r, t, u, w are the same as above. The same below. ) etc. As a more specific structural example, there can be cited: M H 2D 10 、M H 2D 100 、M2D 27 D H 3. M2D 97 D H 3. M2D 26 D H 4. M2D 25 D H 5. M2D 24 D H 6. M2D 96 D H 4. M2D 95 D H 5. M H 3D 100 T1, M H 4D 100 T2, M H 2D 97 D H 1. M2D 30 D H 5Q1, M H 2D 95 D H 3. M3D 93 D H 3T H 1st, etc.
[0041] The weight average molecular weight of component (B) is preferably 194 to 20,000, more preferably 874 to 5,000. If the weight average molecular weight of component (B) is too small, the adhesion may be greatly deteriorated, and if it is too large, the following problems may be found: poor reactivity, reduced curability, reduced residual adhesion, and increased peeling force due to insufficient curing. It should be noted that in the present invention, the weight average molecular weight of component (B) is a weight average molecular weight converted to polystyrene obtained by gel permeation chromatography (GPC) analysis (solvent: toluene).
[0042] The kinematic viscosity of the component (B) at 25° C. measured with an Ostwald viscometer is preferably 2 to 500 mm 2 / s, more preferably 2 to 300 mm 2 / s, more preferably 5 to 200 mm 2 / s. If the kinematic viscosity at 25°C is less than 2 mm 2 / s, because the molecular weight is small, the reactivity is good, but the adhesion to the substrate may be poor. In addition, from the perspective of curing and peeling properties, 500 mm is preferred. 2 / s or less.
[0043] The amount of component (B) is preferably such that the number of moles of Si-H groups is equivalent to 1 to 5 times the number of moles of alkenyl groups in component (A), and more preferably to 1.2 to 3 times. The amount equivalent to 1 to 5 times is equivalent to 0.016 to 3.5 mol / 100 g based on the amount of Si-H functional groups. If the amount of component (B) is too little, the curing property and adhesion may be insufficient. If the amount of component (B) is too much, the amount of remaining Si-H groups increases, resulting in an increase in the peeling force. The Si-H groups decrease over time, so the peeling force may decrease over time.
[0044] [(C) ingredient] As the (C) platinum group metal catalyst of the present invention, a known platinum group metal catalyst used as an addition reaction catalyst can be used. As such a platinum group metal catalyst, for example, catalysts such as platinum, palladium, rhodium, and ruthenium can be mentioned, among which platinum catalysts are particularly preferably used. As the platinum catalyst, for example, platinum compounds, complexes of platinum and vinyl siloxane, alcohol solutions or aldehyde solutions of chloroplatinic acid, complex salts of chloroplatinic acid and various olefins, complexes of chloroplatinic acid and vinyl siloxane, etc. can be mentioned.
[0045] The amount of component (C) is 1 to 200 ppm, preferably 1 to 100 ppm, more preferably 2 to 70 ppm, further preferably 3 to 50 ppm, and particularly preferably 7 to 25 ppm, based on the mass conversion of the platinum group metal relative to the total amount of the composition. In the present invention, curing can be achieved with a small amount of catalyst, so the amount can be made smaller.
[0046] [(D) ingredient] The (D) addition reaction control agent of the present invention is a component that is formulated as needed to control the catalytic activity of the platinum group metal catalyst, and examples thereof include: various organic nitrogen compounds, organic phosphorus compounds, acetylene compounds, oxime compounds, organic chlorine compounds, etc. Among them, a mixture of an acetylene-containing compound having a hydroxyl group and an acetylene-containing silane is preferred. The reasons for its excellence are as follows. The acetylene-containing compound having a hydroxyl group itself has an excellent effect of controlling the addition reaction, but is insoluble in siloxane compounds, and therefore cannot fully exert its ability. Therefore, by using it in combination with an acetylene-containing silane that is compatible with siloxane compounds, the compatibility of the acetylene-containing compound having a hydroxyl group is improved, so that the control effect it has can be fully exerted. In addition, the reason is that when heated, the acetylene-containing compound having a hydroxyl group is azeotropically co-existing with the acetylene-containing silane having a low boiling point, so that the control agent is no longer present in the composition at a temperature lower than the original temperature.
[0047] Examples of the acetylene group-containing compound having a hydroxyl group include 1-ethynyl-1-cyclohexanol, 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-pentyn-3-ol, and 2-phenyl-3-butyn-2-ol.
[0048] Examples of the silane having an acetylene group include reaction products of acetylene compounds such as 1,1-dimethylpropynyloxytrimethylsilane and dimethylbis(1,1-dimethyl-2-propynyloxy)silane and alkoxysilane.
[0049] The amount of the component (D) when added is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the component (A).
[0050] [Optional Ingredients] In the organopolysiloxane composition of the present invention, components that are usually incorporated into an organopolysiloxane composition for release paper or release film can be incorporated within a range that does not impair the effects of the present invention. It should be noted that their properties will not be reduced even when they are diluted in an organic solvent during use. In the present invention, a solvent-free organopolysiloxane composition is preferred. The amount of components other than the above-mentioned (A) to (D) components is appropriately selected within a range that does not impair the effects of the present invention, for example, it can be appropriately selected from 0.001 to 990 parts by mass, preferably 1 to 100 parts by mass, relative to 100 parts by mass of component (A).
[0051] Examples of the organic solvent include organic solvents soluble in organopolysiloxane (excluding siloxane solvents) such as toluene, hexane, xylene, and methyl ethyl ketone (also known as 2-butanone), and low-viscosity cyclic siloxanes such as octamethylcyclotetrasiloxane and decamethylcyclopentasiloxane, and organopolysiloxane (siloxane solvents).
[0052] As the optional added components, for example, for the purpose of imparting slip properties, high molecular weight linear organopolysiloxanes other than components (A) and (B) may be mentioned, and for the purpose of adjusting the peeling force, silicone resins having aromatic groups other than components (A) and (B), silicone resins, silica, and low molecular weight organopolysiloxanes having neither hydrogen atoms bonded to silicon atoms nor alkenyl groups may be mentioned.
[0053] [Manufacturing method and optional ingredients] The organopolysiloxane composition of the present invention can be obtained, for example, by mixing the above-mentioned components (A-1), (A-2), (B) and (C). The process of mixing (A-1), (A-2) and (B) may be further mixed with component (D). In addition, (A-1) and (A-2) may be pre-mixed. It should be noted that in the case of mixing component (D), it is preferred to have a process of pre-mixing and dispersing component (D) in components (A-1) and (A-2) or (B). Specifically, a product is prepared by pre-mixing and dispersing component (D) in components (A-1) and (A-2) or (B), which is incompatible with the organopolysiloxane, and uniformly dispersing it, and then mixing the remaining components, so that the addition reaction control agent can be uniformly dispersed.
[0054] [Addition reaction curing type organopolysiloxane composition] The organopolysiloxane composition of the present invention is an addition reaction curing type. From the viewpoint of having the above-mentioned properties, it is suitable for use as a release paper or a release film. The kinematic viscosity of the addition reaction curing type organopolysiloxane composition of the present invention at 25° C. measured by an Ostwald viscometer is preferably 500 mm 2 / s or less, more preferably 10 to 450 mm 2 / s, more preferably 50 to 430 mm 2 If the kinematic viscosity is too low, the coating amount may be reduced, and if the kinematic viscosity is too high, the coating amount may be uneven or a large amount of mist may be generated.
[0055] The peeling force of the organopolysiloxane composition of the present invention was evaluated by the FINAT method described in the examples using a TESA-7475 tape. At this time, the peeling force was evaluated at 25°C and 70 gf / cm 2 Under load and 70℃, 20gf / cm 2 In any case under a load of , the peel force is preferably 0.01 to 1 N / 25 mm, more preferably 0.03 to 0.5 N / 25 mm.
[0056] [Purpose and How to Use] The organopolysiloxane composition of the present invention is coated on a sheet substrate such as paper or a plastic film by a coating roller, and then cured by heating by a conventional method. In this way, a cured silicone film of the organopolysiloxane composition of the present invention is formed on one side of the sheet substrate, which is suitable for use as a release sheet for release paper or release film. Examples of paper substrates include glassine paper, polyethylene laminated paper, polyvinyl alcohol resin coated paper, and clay coated paper. Examples of plastic film substrates include films of polyesters such as polyethylene, polypropylene, and polyethylene terephthalate.
[0057] [For release paper or release film] A release paper or a release film having a cured product of the organopolysiloxane composition of the present invention can be obtained. For example, the amount of the organopolysiloxane composition applied is sufficient to form a cured silicone film on the surface of the sheet substrate, for example, 0.1 to 5.0 g / m 2 Too much coating may lead to a decrease in peeling performance. The temperature during heat curing varies depending on the type of substrate and the coating amount. By heating at 60 to 200°C, preferably 100 to 190°C, more preferably 120 to 180°C for 1 to 60 seconds, more preferably 2 to 40 seconds, a cured film can be formed on the substrate. Example
[0058] The following examples and comparative examples are shown to specifically illustrate the present invention, but the present invention is not limited to the following examples. 29 The viscosity was obtained by Si-NMR and was measured using a rotational viscometer at 25°C. The kinematic viscosity was measured using an Ostwald viscometer at 25°C.
[0059] [Raw materials used] (A) (A-1)Ingredients (A-1-1) Siloxane containing vinyl groups at both ends: M Vi 2D 155 M Vi :(CH2=CH)(CH3)2SiO 1 / 2 D: (CH3)2SiO 2 / 2 <Synthesis method> In 1,3-divinyltetramethyldisiloxane (M Vi2) KOH (300 ppm) was added to 0.1 mol and 3.875 mol of octamethylcyclotetrasiloxane (D4), and polymerization and equilibration were carried out at 150°C for 6 hours. Then, 1.5 times the mol of chloroethanol as much as KOH was added, and neutralization was carried out at 150°C for 3 hours. After 3 hours of reduced pressure concentration at 120°C and 20 mmHg, 5% by mass of activated carbon Silasagi A (manufactured by Osaka Gas Chemical Co., Ltd.) was added, and after stirring for 2 hours, filtration was performed using a filter plate NA10 (manufactured by ADVANTEC). The obtained siloxane was filtered through 29 Si-NMR determination shows that the structural formula is: M Vi 2D 155 The molecular chain shown is terminated at both ends with dimethylvinylsiloxy groups, and all other parts except the two ends are composed of (CH3)2SiO units. The vinyl value is 0.017 mol / 100 g and the kinematic viscosity is 440 mm 2 / s of organopolysiloxane.
[0060] (A-1-2) Siloxane containing vinyl groups at both ends: M Vi 2D 100 M Vi :(CH2=CH)(CH3)2SiO 1 / 2 D: (CH3)2SiO 2 / 2 <Synthesis method> In 1,3-divinyltetramethyldisiloxane (M Vi 2) KOH (300 ppm) was added to 0.1 mol and 2.5 mol of octamethylcyclotetrasiloxane (D4), and polymerization and equilibration were carried out at 150°C for 6 hours. Then, 1.5 times the mol of chloroethanol as much as KOH was added, and neutralization was carried out at 150°C for 3 hours. After 3 hours of reduced pressure concentration at 120°C and 20 mmHg, 5% by mass of activated carbon Silasagi A (manufactured by Osaka Gas Chemical Co., Ltd.) was added, and after stirring for 2 hours, filtration was performed using a filter plate NA10 (manufactured by ADVANTEC). The obtained siloxane was filtered through 29 Si-NMR determination shows that the structural formula is: M Vi 2D 100 The molecular chain shown is terminated at both ends with dimethylvinylsiloxy groups, and all other ends are composed of (CH3)2SiO units, the vinyl value is 0.026 mol / 100 g, and the kinematic viscosity is 200 mm 2 / s of organopolysiloxane.
[0061] (A-2)Ingredients (A-2-1) Siloxane containing side chain acryloyl groups and vinyl groups at both ends: M Vi 2D90 D Ac 1 D: (CH3)2SiO 2 / 2 , D Ac (CH2=CHCOOCH2CH2CH2)(CH3)SiO 2 / 2 <Synthesis method> In 1,3-divinyltetramethyldisiloxane (M Vi 2) 0.1 mol, octamethylcyclotetrasiloxane (D4) 2.25 mol and tetramethyltetraacryloxycyclotetrasiloxane (D Ac 4) Add 10% by mass of sulfuric acid based on the total amount of siloxane to 0.025 mol, and perform polymerization and equilibration at room temperature for 4 hours. Add 2% by mass of water and 82.5% by mass of toluene based on the total amount of siloxane, stir for 2 hours and then let stand. After separating the organic layer and the aqueous layer, recover and discard the aqueous layer. Add about 80% by mass of 10% by mass of Glauber's salt water to the organic layer, stir for 30 minutes and then let stand. Then, discard the separated aqueous layer. Add about 3% by mass of Glauber's salt based on the total mass of siloxane, dehydrate and filter with a filter plate. The obtained siloxane is subjected to reduced pressure stripping at 120°C and 10 mmHg to obtain a viscosity of 205 mm 2 / s, and an organopolysiloxane with a volatile content of 3.2% by mass. 1 The vinyl value calculated by H-NMR was 0.028 mol / 100 g.
[0062] (A-2-2) Siloxane containing side chain acryloyl groups and vinyl groups at both ends: M Vi 2D 90 D Ac 9 In 1,3-divinyltetramethyldisiloxane (M Vi 2) 0.1 mol, octamethylcyclotetrasiloxane (D4) 2.25 mol and tetramethyltetraacryloxycyclotetrasiloxane (D Ac 4) Add 10% by mass of sulfuric acid based on the total amount of siloxane to 0.225 mol, and perform polymerization and equilibration at room temperature for 4 hours. Add 2% by mass of water and 82.5% by mass of toluene based on the total amount of siloxane, stir for 2 hours and then let stand. After separating the organic layer and the aqueous layer, recover and discard the aqueous layer. Add about 80% by mass of 10% by mass of Glauber's salt water to the organic layer, stir for 30 minutes and then let stand. Then, discard the separated aqueous layer. Add about 3% by mass of Glauber's salt based on the total amount of siloxane, dehydrate and filter with a filter plate. The obtained siloxane is subjected to reduced pressure stripping at 120°C and 10 mmHg to obtain a viscosity of 231 mm 2 / s, and an organopolysiloxane with a volatile content of 3.3% by mass. 1The vinyl value calculated by H-NMR was 0.024 mol / 100 g.
[0063] (A-2-3) Siloxane containing side chain acryloyl groups and vinyl groups at both ends: M Vi 2D 150 D Ac 0.1 In 1,3-divinyltetramethyldisiloxane (M Vi 2) 0.1 mol, octamethylcyclotetrasiloxane (D4) 2.25 mol and tetramethyltetraacryloxycyclotetrasiloxane (D Ac 4) Add 0.7 mass % of trifluoromethanesulfonic acid and 0.05 mass % of 2,6-di-tert-butyl-4-methylphenol (Ionol: manufactured by Oxalis Chemical Co., Ltd.) to 0.225 mol of the total amount of siloxane, and polymerize and equilibrate at 60°C for 8 hours. After equilibration, add Kyoward 500SH (neutralizing agent; hydrotalcite: manufactured by Kyowa Chemical Industry Co., Ltd.) in an amount twice that of the catalyst, and stir for 2 hours to neutralize. After neutralization, separate the solid substances such as Kyoward 500SH and siloxane by filtration using a filter plate. The obtained siloxane is subjected to reduced pressure stripping at 120°C and 10 mmHg to obtain a viscosity of 415 mm 2 / s, and an organopolysiloxane with a volatile content of 3.1% by mass. 1 The vinyl value calculated by H-NMR was 0.0177 mol / 100 g.
[0064] (B) Ingredients (B-1) Methyl hydrogen polysiloxane The molecular chain is terminated with trimethylsiloxy groups at both ends, and all other ends are composed of (CH3)HSiO units. The Si-H group content is 1.54 mol / 100g and the kinematic viscosity is 32 mm 2 / s methyl hydrogen polysiloxane
[0065] (C) Ingredients (C-1) Platinum group metal catalyst: complex of platinum and vinylsiloxane
[0066] (D) Ingredients (D-1) 1-ethynyl-1-cyclohexanol (D-2) Dimethylbis(1,1-dimethyl-2-propynyloxy)silane
[0067] [Example 1] 50 parts by mass of methylvinylpolysiloxane (A-1-1) as component (A-1), 50 parts by mass of siloxane (A-2-1) containing vinyl groups at both ends of side chain acryl groups as component (A-2), 1 part by mass of 1-ethynylcyclohexanol (D-1) as component (D), and 0.5 parts by mass of dimethylbis(1,1-dimethyl-2-propynyloxy)silane (D-2) as component (D) were added, and 2.34 parts by mass of methylhydrogenpolysiloxane (B-1) as component (B) were added to the mixture stirred for 10 minutes until it became uniform, and mixed for 10 minutes. Then, 0.52 parts by mass of a complex of platinum and vinylsiloxane (C-1) as component (C) was added so that the total mass of components (A), (B), and (D) was 13 ppm in terms of the mass of platinum atoms, and stirred for 1 minute until it became uniform, and a composition having H / Vi (the ratio of Si-H groups in the composition to alkenyl groups in the composition) = 1.6 was prepared. The amount of cyclic low molecular weight siloxane (D4+D5+D6) contained in (A) was 700 ppm.
[0068] [Example 2] A composition having H / Vi=1.6 was prepared in the same manner as in Example 1 except that 95 parts by mass of methylvinylpolysiloxane (A-1-1) was used as component (A-1), 5 parts by mass of siloxane (A-2-2) containing vinyl groups at both ends of side chain acryl groups was used as component (A-2), and 1.80 parts by mass of methylhydrogenpolysiloxane (B-1) was used as component (B). The amount of cyclic low molecular weight siloxane contained in (A) was 740 ppm.
[0069] [Example 3] A composition having H / Vi=1.6 was prepared in the same manner as in Example 1 except that 50 parts by mass of methylvinylpolysiloxane (A-1-2) was used as component (A-1), 50 parts by mass of siloxane (A-2-1) containing vinyl groups at both ends of side chain acryl groups was used as component (A-2), and 2.81 parts by mass of methylhydrogenpolysiloxane (B-1) was used as component (B). The amount of cyclic low molecular weight siloxane contained in (A) was 710 ppm.
[0070] [Example 4] A composition having H / Vi=1.6 was prepared in the same manner as in Example 1 except that 99.5 parts by mass of methylvinylpolysiloxane (A-1-2) was used as component (A-1), 0.5 parts by mass of siloxane (A-2-2) containing vinyl groups at both ends of side chain acryl groups was used as component (A-2), and 2.70 parts by mass of methylhydrogenpolysiloxane (B-1) was used as component (B). The amount of cyclic low molecular weight siloxane contained in (A) was 40 ppm.
[0071] [Comparative Example 1] 100 parts by mass of methylvinylpolysiloxane (A-1-1) as component (A-1), 1.77 parts by mass of methylhydrogenpolysiloxane (B-1) as component (B), 1 part by mass of 1-ethynylcyclohexanol (D-1) as component (D), and 0.5 parts by mass of dimethylbis(1,1-dimethyl-2-propynyloxy)silane (D-2) as component (D) were added, stirred for 10 minutes, and then 0.52 parts by mass of a complex of platinum and vinylsiloxane as component (C) was added so that the total mass of components (A), (B), and (D) was 13 ppm in terms of platinum atomic mass, and stirred for 1 minute to prepare a composition having H / Vi (ratio of Si-H groups in the composition to alkenyl groups in the composition) = 1.6. The amount of cyclic low molecular weight siloxane contained in (A) was 20 ppm.
[0072] [Comparative Example 2] 100 parts by mass of methylvinylpolysiloxane (A-1-2) as component (A-1), 2.70 parts by mass of methylhydrogenpolysiloxane (B-1) as component (B), 1 part by mass of 1-ethynylcyclohexanol (D-1) as component (D), and 0.5 parts by mass of dimethylbis(1,1-dimethyl-2-propynyloxy)silane (D-2) as component (D) were added, stirred for 10 minutes, and then 0.52 parts by mass of a complex of platinum and vinylsiloxane as component (C) was added so that the total mass of components (A), (B) and (D) was 13 ppm in terms of the mass of platinum atoms, and stirred for 1 minute to prepare a composition having H / Vi (ratio of Si-H groups in the composition to alkenyl groups in the composition) = 1.6. The amount of cyclic low molecular weight siloxane contained in (A) was 30 ppm.
[0073] [Comparative Example 3] 100 parts by mass of siloxane (A-2-1) containing vinyl groups at both ends of a side chain acryl group as component (A-2), 2.9 parts by mass of methyl hydrogen polysiloxane (B-1) as component (B), 1 part by mass of 1-ethynylcyclohexanol (D-1) as component (D), and 0.5 parts by mass of dimethylbis(1,1-dimethyl-2-propynyloxy)silane (D-2) as component (D) were added, and stirred for 10 minutes. After that, 0.52 parts by mass of a complex of platinum and vinylsiloxane as component (C) was added so that the total mass of components (A), (B), and (D) was 13 ppm in terms of the mass of platinum atoms, and stirred for 1 minute to prepare a composition having H / Vi (ratio of Si-H groups in the composition to alkenyl groups in the composition) = 1.6. The amount of cyclic low molecular weight siloxane contained in (A) was 1390 ppm.
[0074] [Comparative Example 4] 100 parts by mass of siloxane (A-2-2) containing vinyl groups at both ends of a side chain acryloyl group as component (A-2), 2.49 parts by mass of methyl hydrogen polysiloxane (B-1) as component (B), 1 part by mass of 1-ethynylcyclohexanol (D-1) as component (D), and 0.5 parts by mass of dimethylbis(1,1-dimethyl-2-propynyloxy)silane (D-2) as component (D) were added, and stirred for 10 minutes. After that, 0.52 parts by mass of a complex of platinum and vinylsiloxane as component (C) was added so that the total mass of components (A), (B), and (D) was 13 ppm in terms of the mass of platinum atoms, and stirred for 1 minute to prepare a composition having H / Vi (ratio of Si-H groups in the composition to alkenyl groups in the composition) = 1.6. The amount of cyclic low molecular weight siloxane contained in (A) was 14510 ppm.
[0075] [Comparative Example 5] 100 parts by mass of siloxane (A-2-3) containing vinyl groups at both ends of a side chain acryl group as component (A-2), 1.84 parts by mass of methyl hydrogen polysiloxane (B-1) as component (B), 1 part by mass of 1-ethynylcyclohexanol (D-1) as component (D), and 0.5 parts by mass of dimethylbis(1,1-dimethyl-2-propynyloxy)silane (D-2) as component (D) were added, and stirred for 10 minutes. After that, 0.52 parts by mass of a complex of platinum and vinylsiloxane as component (C) was added so that the total mass of components (A), (B), and (D) was 13 ppm in terms of the mass of platinum atoms, and stirred for 1 minute to prepare a composition having H / Vi (ratio of Si-H groups in the composition to alkenyl groups in the composition) = 1.6. The amount of cyclic low molecular weight siloxane contained in (A) was 12480 ppm.
[0076] [Comparative Example 6] 20 parts by mass of methylvinylpolysiloxane (A-1-1) as component (A-1), 80 parts by mass of siloxane (A-2-1) containing vinyl groups at both ends of side chain acryl groups as component (A-2), 2.68 parts by mass of methylhydrogenpolysiloxane (B-1) as component (B), 1 part by mass of 1-ethynylcyclohexanol (D-1) as component (D), and 0.5 parts by mass of dimethylbis(1,1-dimethyl-2-propynyloxy)silane (D-2) as component (D) were added, and stirred for 10 minutes. After that, 0.52 parts by mass of a complex of platinum and vinylsiloxane as component (C) was added so that the total mass of components (A), (B), and (D) was 13 ppm in terms of the mass of platinum atoms, and stirred for 1 minute to prepare a composition having H / Vi (ratio of Si-H groups in the composition to alkenyl groups in the composition) = 1.6. The amount of cyclic low molecular weight siloxane contained in (A) was 1120 ppm.
[0077] [Comparative Example 7] 40 parts by mass of methylvinylpolysiloxane (A-1-2) as component (A-1), 60 parts by mass of siloxane (A-2-2) containing vinyl groups at both ends of side chain acryl groups as component (A-2), 2.58 parts by mass of methylhydrogenpolysiloxane (B-1) as component (B), 1 part by mass of 1-ethynylcyclohexanol (D-1) as component (D), and 0.5 parts by mass of dimethylbis(1,1-dimethyl-2-propynyloxy)silane (D-2) as component (D) were added, and stirred for 10 minutes. After that, 0.52 parts by mass of a complex of platinum and vinylsiloxane as component (C) was added so that the total mass of components (A), (B), and (D) was 13 ppm in terms of the mass of platinum atoms, and stirred for 1 minute to prepare a composition having H / Vi (ratio of Si-H groups in the composition to alkenyl groups in the composition) = 1.6. The amount of cyclic low molecular weight siloxane contained in (A) was 8720 ppm.
[0078] The organopolysiloxane compositions obtained in the above examples were evaluated as follows. The results are also shown in the table.
[0079] [Appearance of coating liquid] Each composition of the examples and comparative examples was stirred for 1 minute after the platinum catalyst was added, and the appearance after stirring (mixing) and after standing for 8 hours was visually observed.
[0080] [Peel force] The organopolysiloxane composition was coated on a metal roller of an offset transfer machine (manufactured by IHI Machinery Systems Co., Ltd.), and the metal roller was brought into contact with a rubber roller and rotated for 45 seconds to evenly spread the composition. Then, the composition was transferred from the rubber roller to a glass paper ASP (manufactured by Ahlstrom-Munksjo Co., Ltd.). The glass paper to which the composition was transferred was heated in a hot air dryer at 120°C for 30 seconds to obtain a glass paper having a thickness of 0.9 to 1.1 g / m 2 After aging for 24 hours at 25°C, TESA-7475 tape (tesa UK Ltd) was attached to the cured film surface of the release paper (from the transfer surface of the rubber roller) and cut into a size of 2.5 cm × 18 cm to obtain a test piece. The test piece was clamped on a glass plate and subjected to aging at 25°C and 70 gf / cm 2 Under load and 70℃, 20gf / cm 2 The test piece was aged for 20 hours under a load of . After aging, one end of the test piece was peeled off, and the end of the tape was stretched at a peeling speed of 0.3 m / min in a direction at an angle of 180 degrees relative to the cellophane. At this time, a tensile tester (AGS-50G model, Shimadzu Corporation) was used to measure the force required to peel off the tape (i.e., "peeling force") (N / 25 mm).
[0081] [Residual Adhesion Rate] The TESA-7475 tape after the above peeling force measurement was pasted on a stainless steel plate, and a 2 kg roller was reciprocated once to apply a load. After standing for 30 minutes, one end of the TESA-7475 tape was peeled off, and the end was stretched in a direction of 180 degrees relative to the stainless steel plate. The force required to peel the tape at a peeling speed of 0.3 m / min was measured (hereinafter referred to as "peeling force A", N / 25 mm). As a control, an unused TESA-7475 tape was attached to a stainless steel plate, and a 2 kg roller was reciprocated once to apply a load in the same manner as above. After standing for 30 minutes, one end of the TESA-7475 tape was peeled off, and the end was stretched in a direction at an angle of 180 degrees relative to the stainless steel plate. The force required to peel the tape at a peeling speed of 0.3 m / min (hereinafter referred to as "peeling force B", N / 25 mm) was measured. The residual adhesion ratio (%) was calculated from "(value of peel force A) / (value of peel force B)×100".
[0082] [Curing properties] Using the same method as the above-mentioned peeling force measurement, for each organopolysiloxane composition, the composition was transferred onto a glass paper ASP using an offset transfer machine. The glass paper to which the organopolysiloxane composition was transferred was heated in a hot air dryer at 120°C for 30 seconds to obtain a glass paper having a thickness of 0.9 to 1.1 g / m 2 Remove the release paper from the dryer and immediately rub the surface of the cured film 10 times with your index finger, apply red ink (trade name: Magic ink), and observe the density of the ink and the state of the cured film. Evaluate the results based on the following indicators. “○” Fingerprints are almost invisible The “△” finger marks look shallow The “×” fingerprint looks thick
[0083] [Migration amount of silicone (organopolysiloxane)] Similar to the case of the peeling force measurement, a polyester film with a thickness of 38 μm was placed on the surface of the cured film of the organopolysiloxane composition formed on the surface of the glass paper, and after being pressed at room temperature under a pressure of 0.98 MPa for 20 hours, the polyester film was removed from the cured film. An oil-based ink (trade name: Magicink, manufactured by Teranishi Chemical Industry Co., Ltd.) was applied to the surface of the polyester film that had been in contact with the cured film, and the silicone migration was evaluated based on the shrinkage crater. The results were evaluated based on the following indicators. "○" No cratering of ink (no silicone migration or very small) “×” means there are shrinkage holes in the ink (silicone has high migration potential)
[0084] [Amount of low molecular weight siloxane contained in (A)] 0.1 g of component (A) was extracted with 10 ml of acetone and subjected to gas chromatography to quantify the total amount of cyclic siloxane (octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane). The measurement conditions were: a capillary column, a temperature rise of 50°C to 280°C, helium as carrier gas, an FID as detector, and a sample injection volume of 2 μL.
[0085] [Table 1]
[0086] [Table 2]
[0087] [Table 3]
Claims
1. An addition reaction curable organopolysiloxane composition comprising the following components (A), (B) and (C), (A)The following (A-1) and (A-2) (A-1) an organopolysiloxane having an average of 2 or more alkenyl groups bonded to a silicon atom in one molecule and having no (meth)acryloyl group: 50 to 99.9 parts by mass, (A-2) 50 to 0.1 parts by mass of an organopolysiloxane having an average of 0.1 or more alkenyl groups and an average of 0.1 to 20 (meth)acryloyl groups per molecule, wherein: The total amount of (A-1) and (A-2) is 100 parts by mass, (B) an organohydrogenpolysiloxane having an average of two or more hydrogen atoms (Si—H groups) bonded to silicon atoms in one molecule (C) Platinum group metal catalyst: 1 to 200 ppm in terms of mass of platinum group metal relative to the total amount of the composition.
2. The addition reaction-curable organopolysiloxane composition according to claim 1, wherein The total content of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane is 1000 ppm by mass or less of the component (A). 3 . The addition reaction-curable organopolysiloxane composition according to claim 1 , further comprising an addition reaction control agent as component (D).
4. The addition reaction curable organopolysiloxane composition according to claim 3, wherein The component (D) contains a mixture of an acetylene group-containing compound having a hydroxyl group and a silane having an acetylene group. 5 . The addition reaction-curable organopolysiloxane composition according to claim 1 , which is used for release paper or release film.
6. A method for producing the addition reaction-curable organopolysiloxane composition according to claim 1, comprising the step of mixing the components (A-1), (A-2) and (B).
7. A method for producing the addition reaction-curable organopolysiloxane composition according to claim 3, comprising the step of mixing and dispersing the component (D) in advance in the components (A-1) and (A-2) or (B).
8. The production method according to claim 6 or 7, comprising a step of synthesizing the component (A-1) using a base catalyst and a step of synthesizing the component (A-2) using an acid catalyst.
Citation Information
Patent Citations
Silicone dissociable coating composition
JP2009513740A
Organopolysiloxane composition for use in release paper or release film
WO2020145151A1